Evaluation of clinical and laboratory findings in MIS-C patients associated with COVID-19: An experience from the Northwest of Iran. - Mina Farshidgohar; Sonia Oveisi; Samira Dodangeh; Fatemeh Fawzi; Faezeh Maleki Sanjani; Alireza Razzaghi; Hossein Teimouri; Gerson Nakazato (PLoS ONE)
This study aimed to evaluate the range of clinical and laboratory findings of multisystem inflammatory syndrome in children (MIS-C) with COVID-19 in a tertiary children's hospital in Northwest Iran during 2020-2022. According to the CDC guidelines, this cross-sectional study included 300 pediatric patients diagnosed with MIS-C. Data were collected retrospectively from medical records, focusing on symptoms, organ involvement, laboratory findings, and outcomes. Statistical analysis was performed using SPSS software, with significance set at p-values <0.05. The study population had a median age of 3 years, with a slight male predominance (57.3%). The most affected systems in MIS-C disease were hematological (87%), gastrointestinal (85%), and respiratory (67%). Laboratory analysis highlighted elevated inflammatory markers such as D-dimer (83.3%), ferritin (71.4%), and CRP (49.7%). Abnormal urinalysis was observed in 151 patients (50.3%), with glucosuria in 83 cases (27.7%) and proteinuria in 29 cases (9.7%). The study found a significant correlation between cardiovascular issues and elevated blood platelets, ESR, CRP, and troponin levels (P ≤ 0.01) but not with ferritin, albumin, or D-dimer levels. Also, the examination of disease outcomes in this study revealed that 81.7% of MIS-C patients were isolated during their hospital stay, 18.3% needed ICU care, and 1% died in hospital. We have presented an experience with distinct clinical and laboratory manifestations in MIS-C. Given the lower median age in this study compared to previous studies, reporting clinical and laboratory manifestations of MIS-C in pediatrics with a younger age is valuable for the diagnosis and treatment course. Some laboratory factors were risk factors for cardiovascular involvement, and consequently, echocardiography is recommended in MIS-C patients with these laboratory indications. Given the lack of a specific diagnostic test for this emerging disease, studies focusing on investigating clinical symptoms and findings are valuable.